2023
DOI: 10.1017/s2045796022000774
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of medically serious suicide attempts in France: incidence and associated factors

Abstract: Aims People who make medically serious suicide attempts (MSSAs) share a number of features with those who die by suicide, and are at a high risk of suicide themselves. Studies to date have mostly focused on clinical samples of MSSAs. An epidemiological examination at a national level can help to identify risk profiles and pathways of care in this population. Methods We explored the French nationwide hospital discharge database (Programme de Médicalisation des Systèmes d'Information, PMSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
3
1
0
Order By: Relevance
“…This result can be explained because MSSA can be studied as a subgroup, which differs from SA, not only because of the high lethality but also in view of the differential sociodemographic characteristics (36-38). Moreover, these data agree with Corbé et al 27 , who found that women represent half of MSSA cases out of a total sample of 81,959. Previous SA is the only predictive factor of suicide found (38), with Ammerman et al 33 stressing the need to implement suicidal risk screening in order to identify those who are at risk of suicide.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result can be explained because MSSA can be studied as a subgroup, which differs from SA, not only because of the high lethality but also in view of the differential sociodemographic characteristics (36-38). Moreover, these data agree with Corbé et al 27 , who found that women represent half of MSSA cases out of a total sample of 81,959. Previous SA is the only predictive factor of suicide found (38), with Ammerman et al 33 stressing the need to implement suicidal risk screening in order to identify those who are at risk of suicide.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning age, our data concurred with Corbé et al 27 who found a higher number of caseloads represented in the age group from 25-55 years old (27). Despite that, the literature reported an increase in SA in the elderly during the COVID period, associated with more vulnerability, lower economic inputs, and isolation (33,34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the methods of suicide, we uncovered statistically significant differences in terms of gender; men used methods that are more violent, while women used poisoning more frequently. This is in line with the data reported in France, where deliberate poisoning was more frequent in women and men who used methods related to a high likelihood of death [ 24 ]. In that study, the most frequent diagnoses were substance use and mood disorders.…”
Section: Discussionsupporting
confidence: 92%